A Case Study of Deep DNAPL Contamination in Marine Soft Clays. (13th February 2023) - Gao, Yanbin; Ji, Wenqi; Li, Tao
Abstract : Aquifers in China's southeast coastal areas are protected by the overlying marine soft clays formed in Holocene transgression. However, a fundamental understanding of the characteristics of DNAPL (dense nonaqueous phase liquid) contamination in marine soft clays is limited. The study was conducted on the site of a former pharmaceutical factory in Shanghai, where serious 1, 1, 2-trichloroethane (DNAPL) contamination was detected up to the depth of 22.0 m below the existing grade. Partitioning calculation method was used to identify the presence of pure phase, and the results showed that pure 1, 1, 2-trichloroethane was accumulated at the interface of the upper soft silty clay and lower soft clay. The vertical transport was believed to be the pure DNAPL displacing pore water following the principle of two-phase flow, rather than the convection and diffusion of aqueous phase. The contamination (NAPL-soil interaction) impacted the soil properties slightly, and this effect could not account for the deep contamination. Soil structure analysis showed that these clays contained a proportion of large interaggregate pores, providing pathways for the transport of pure DNAPL. Considering their flocculated structure, the marine soft clays are not capable to perform as a barrier to prevent the downward migration of pure DNAPL.